Interaction of hypoxia and vascular occlusion on cardiorespiratory responses during exercise - Keller-Ross,. L.; Sarkinen, A. L.; Chantigian, D. P.; Cross, T. J.; Johnson, B. D.; Olson, T. P. (Translational Sports Medicine, 2019)
The interaction of group III/IV afferents and chemoreflex during exercise is critical in healthy adults during high altitude exercise or in clinical populations who experience hypoxia. Purpose: Investigate the cardiorespiratory response to simultaneous vascular occlusion (to activate group III/IV afferents) and hypoxia (to activate chemoreflex) during cycling exercise. Methods: 18 adults (9 women, 25±5 yr) attended two sessions. Session 1: maximal cycle ergometry test. Session 2: two 26-minute bouts (randomized between hypoxia, 12.5% FiO2 and normoxia, 21% FiO2). Participants cycled at 30% of peak workload for 3min (control, CTL) followed by alternating 2min periods of bilateral vascular occlusion of the proximal thigh at pressures of 20, 40, 60, 80, 100mmHg in a randomized sequence. Results: Ventilation (VE) increased from CTL to 100 mmHg during hypoxia (39±9 to 51±16L/min) and normoxia (31±7 to 39±9L/min, p<0.01). Respiratory rate increased with vascular occlusion (p<0.05) but not hypoxia (p=0.10). Tidal volume was greater during hypoxia (p<0.05), with no influence of vascular occlusion (p=0.40). Mean arterial pressure and heart rate increased more with hypoxia compared with normoxia (p<0.05). Conclusions: Our findings suggest that vascular occlusion and hypoxia both increase VE, albeit via different mechanisms. While hypoxia increased tidal volume, vascular occlusion increased respiratory rate.